Pengaruh Lama Penyinaran Sinar Ultra Violet (UV) Terhadap Kandungan Gizi Pada Es Krim Susu Kedelai - Une, Suryani; Liputo, Siti Aisa; Mutsyahidan, Arif Murtaqi Akhmad; Ahmad, Rahmatia; Ismail, Nurdike; Sidiki, Moh. Rivaldi; Makalalag, Anjely; Supu, Rizky (Universitas Negeri Gorontalo, 2024)
Ice cream is a food product that contains fat ranging from 10-16% which comes from milk. This research aims to determine the damage to ice cream caused by long periods of exposure. The design carried out in this research included a Completely Randomized Design (CRD) with different UV exposure factors. Data were analyzed using statistical tests (ANOVA). Test parameters include peroxide value testing. Based on the research obtained, the peroxide value at a 0 minute exposure time produces 1.15 meq/kg, at a 5 minute exposure time it produces 8.32 meq/kg, at a 10 minute exposure time it produces 10.62 meq/kg and at a exposure time of 15 minutes produces 12.59 meq/kg.